Pola Kerontokan Buah Tiga Kultivar Mangga - , Sakhidin; Bambang S . Purwoko; Roedhy Poerwanto; Slamet Susanto; Sudirman Yahya; Ahmad S. Abidin (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2004)
Information on the pattern of fruit drop of mango is required to determine the appropriate method and time in reducing fruit drop. By this methodf, fruit retention or number of harvested fruit of mango can be increased.The aim of this research was to determine the pattern of fruit drop of Gadung 21, Manalagi 69 and Golek 3 I . The results of this researchs howedt hat the pattern of fruit drop of Gadung2 1, Golek 31 and Manalagi 69 was similar. All cultivars I showed that there was one peak (the highest number of fruit drop) in fruit drop. It occurred at 6 days after anthesis (DAA). After 24 DAA, the number offruit drop was constant, namely near to zero. It occurred until harvest.Key words: Mango, Fruit drop, Fruit set